Prevalence and Outcome of Admission of Preterm Neonates: A Hospital Based Study at the Tertiary Care Center in Rural Nepal - Shrestha, Sandeep; Sindan, Namrata; Kayastha, Nirajana; Thani, Kamal Prasad; Jha, Khushbu; Pahadi, Nirmala; Shrestha, Annie (Journal of Karnali Academy of Health Sciences, 2021)
Background: Preterm births are one of the leading causes of perinatal mortality and morbidity despite of recent advances. It causes long-term medical problem for affected children, the financial burden for their families as well as the health care system of country. The objective and aim of the present study was to identify prevalence and outcome of preterm admissions attending a tertiary care centre in rural Nepal, Jumla.Methods: A retrospective study was carried out on 52 preterm births which were admitted at the Neonatal Intensive Care Unit (NICU) and Special Newborn Care Unit (SNCU) of the Karnali Academy of Health Sciences (KAHS), Jumla from January 2020 to December 2020. This study was carried out from March 2021 to July 2021 for 5 months. All the data were recorded and then analyzed using Statistical Package for Social Sciences (SPSS) version 16. P-value